MASJID MIFTAHUL HUDA KASIMAN BOJONEGORO TAHUN 1926: TINJAUAN SEJARAH, ARSITEKTUR DAN PERANANNYA - Ulfatul Afifah (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2026)
Since the time of the Prophet Muhammad Saw., mosques have served as centers for various activities, such as da’wah, education, deliberation, and, of course, worship. Indonesia has many long-standing mosques classified as historic mosques, such as the Miftahul Huda Kasiman Mosque in Bojonegoro, built in 1926, which is the subject of this study. This study aims to trace the history of the mosque’s establishment by Kiai Asfan, examine the development of the mosque’s architecture and the factors influencing it, and analyze the role or function of the mosque within the surrounding community. This is a qualitative study employing historiographical methodology for its historical analysis, alongside Architectural Theory and the Sociological Theory of Functionalism. The results indicate that the history of the Miftahul Huda Mosque began with a small prayer hall established in 1926 and transitioned into a mosque in 1945 in response to the growing needs of the congregation and the local socio-political context. Its architectural development reflects a continuity of local traditions alongside elements of renewal. Prior to the 2014 renovation, the mosque featured Javanese characteristics, whereas after 2014, it underwent a simplification of its form and the arrangement of its supporting elements and ornamentation. Functionally, the mosque serves as a center for worship as well as education, social integration, and the preservation of traditional values within the community of Bandar Hamlet, Batokan Village, Kasiman, Bojonegoro.